Low dimensional attractors in discharges of sensory neurons of the rat spinal dorsal horn are maintained by supraspinal descending systems - Debus, Stephan; Sandkühler, Jürgen (Neuroscience, 1996)
Background activity was recorded from sensory neurons in laminae I-V of the lumbar spinal dorsal horn of the rat prior to and during cold block spinal…
Online 8 December 1999
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.05.2021